A SKILLS MEASUREMENT MODEL FOR THE SOUTH AFRICAN ENERGY SECTOR: APPLYING THE ANALYTIC HIERARCHY PROCESS TO THE SOUTH AFRICAN ELECTRIC POWER INDUSTRY - Meyer, Markus; Sunjka, Bernadette Patricia (The South African Journal of Industrial Engineering, 2019)
The need to understand the skills value inherent in a project in the South African electrical power sector lies at the core of addressing various skills-related challenges in this sector; and this can hamper the effective implementation of projects. In this study, a model was developed, based on the analytic hierarchy process (AHP), in which three different power generating projects were compared for their skills values at the feasibility stage. A hierarchy was developed, based on identified criteria and sub-criteria. This model was applied by various specialists in an industry-based scenario, where three different types of power generating projects (coal-fired power, nuclear power, and wind power) were compared for their skills values, with the goal of identifying the project that had the highest skills value. This process was conducted through individual guided survey questionnaires with each participant, together with tests, to determine the consensus of the participants. A sensitivity analysis determined that the validity and accuracy of the final result were acceptable. Coal-fired power generation projects were adjudicated as having the highest skills value, followed by nuclear, and then solar.